INFORMATION AND ANALYTICAL SUPPORT FOR ENTERPRISE RESOURCE MANAGEMENT FROM THE STANDPOINT OF ECONOMIC SECURITY - KRYVDYK, Mykhailo; PYATNYCHKA, Mykhaylo; LISOVSKY, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines resource provision as a key factor in the efficiency of industrial enterprises under unstable market conditions, aggravated by risks caused by war. It is substantiated that the availability of sufficient resources ensures the ability of enterprises to adapt to changes, maintain competitiveness, and ensure sustainable development. The focus is placed on the fact that modern realities require not only efficient resource management but also close integration with economic security systems to minimize internal and external threats. The article provides a comparative analysis of existing classifications of resources proposed by leading scholars, identifying their strengths and limitations. Based on a critical rethinking of existing approaches, the author proposes a new classification of enterprise resources that takes into account current challenges, including digitalization, environmental sustainability, social responsibility, and the growing role of reputation. The proposed classification reflects the diversity of resources by origin, composition, ownership, activity type, level of scarcity, area of use, and duration of engagement. Special attention is given to modern resource categories—digital, reputational, partnership, and crisis resources—which directly influence the provision of economic security. It is determined that the proposed classification can serve as a foundation for forming effective resource management strategies aimed at strengthening the enterprise’s competitive advantages and resilience in a turbulent environment. Future research is expected to focus on developing models for integrating economic security systems into resource management processes of industrial enterprises.